Literature Review The Effect of Fish Nuggets on Weight and Height Increase in Toddlers - Lestari, Karisma; Qadrijati, Isna; Kartikasari, Lilik Retna (Nusantara Science and Technology Proceedings, 2024)
The high prevalence of malnutrition and stunting in Indonesia is evidence of a lack of protein consumption in toddlers. One source of protein that has the perfect protein content is fish because fish contains essential amino acids that meet the needs of the body. The lack of fish processing that is in demand by toddlers is the reason for the lack of fish consumption in Indonesia. Fish consumption in Indonesia is shown to be lower than in Singapore and Malaysia. Nuggets are one of the processed foods that are in demand by children because of their various shapes. It is expected that many studies on the effect of fish-based Nuggets can be used as PMT for toddlers with malnutrition and stunting. Objective: Analyzing the effect of giving fish nuggets to increase weight and height in toddlers. Methods: This study is a literature review sourced from Google Scholar, PubMed, Proquest, and ScienceDirect related to the effect of giving fish nuggets on the weight and height of toddlers. The Data used in the literature review is research conducted over the past 10 years. Results and discussion: from the results of the selected articles obtained several 4 by the criteria and in line with the objectives of the study. Conclusion: there is an effect of giving fish nuggets to toddler weight and there is no effect of giving fish nuggets to toddler height.